Design Research: Off the Rails or on the Right Track?. Issue 1 (20th February 2018) - Huber, Amy
Abstract : If research findings remain unknown, they are unlikely to improve design processes and outcomes. While design scholars have lamented the lack of research utilization by practitioners, some designers have derided their efforts. While scholars have outlined strategies to decrease the research utilization gap, these are largely one‐sided suggestions and have lacked widespread implementation and testing. As such, a great deal of information likely remains out of the hands of those who could use it when making decisions that have real‐world implications. To determine a common understanding and collective direction surrounding design research utilization, this article synthesizes existing literature from social science, business, and information management, along with relevant findings from two national surveys. Using this evidence, this article proposes a model framed by economics and aimed at decreasing the research utilization gap prevalent in design. It calls for action on the part of both research producers and consumers and highlights specific issues, including topic selection, information translation, dissemination efforts, increasing awareness, value identification, and factors of action. The goal is for all parts of the design community to share in the responsibility for informing each other, thus growing our collective knowledge.